2004
DOI: 10.1002/art.20157
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase 2–derived prostaglandin E2 production by corticotropin‐releasing hormone contributes to the activated cAMP response element binding protein content in rheumatoid arthritis synovial tissue

Abstract: Objective. To determine a mechanism by which corticotropin-releasing hormone (CRH) promotes human inflammatory joint disease progression.Methods. An ex vivo synovial tissue culture system was established to investigate the functional properties of CRH at peripheral sites of inflammation. CRHand interleukin-1␤ (IL-1␤)-induced prostaglandin E 2 (PGE 2 ) production from 10 fresh rheumatoid arthritis (RA) synovial tissue (ST) explants was quantified using a competitive enzyme-linked immunosorbent assay. Modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 47 publications
0
32
0
1
Order By: Relevance
“…Primary PsA synoviocyte cells were found to be morphogically homogenous fibroblast-like cells and did not react with specific Abs to the macrophage/monocyte Ag CD14. The immortalized normal human K4 IM synoviocyte cell line was grown as described previously (39,57,58). Primary human microvascular endothelial cells (BioWhittaker) were grown using EGM-MV BulletKit (BioWhittaker) (58).…”
Section: Cell Culturementioning
confidence: 99%
See 3 more Smart Citations
“…Primary PsA synoviocyte cells were found to be morphogically homogenous fibroblast-like cells and did not react with specific Abs to the macrophage/monocyte Ag CD14. The immortalized normal human K4 IM synoviocyte cell line was grown as described previously (39,57,58). Primary human microvascular endothelial cells (BioWhittaker) were grown using EGM-MV BulletKit (BioWhittaker) (58).…”
Section: Cell Culturementioning
confidence: 99%
“…The immortalized normal human K4 IM synoviocyte cell line was grown as described previously (39,57,58). Primary human microvascular endothelial cells (BioWhittaker) were grown using EGM-MV BulletKit (BioWhittaker) (58). All cells were grown in serum-free medium for 24 h before stimulation.…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Locally, the CRH levels are increased in the joints of experimental arthritis (in Lewis rats) and in the synovium and synovial fluid of RA patients. 5,6 In situ CRH increases the cycloxygenase-2 derived prostaglandins E2 and E1 locally, thus promoting joint disease progression 7 and pain perception. 8 Baerwald et al (2000) 9 studied the genetic polymorphisms in the promoter region of the CRH gene among Caucasian (UK) and South African black RA patients and found that haplotype A2B1 was protective against developing RA in UK patients whereas allele A1B1 was positively associated with RA in the black South African RA patients (OR=1.78; CI= 1.01-3.15).…”
Section: Introductionmentioning
confidence: 99%